A superhydrophobic chip integrated with an array of medium reservoirs for long-term hanging drop spheroid culture. (November 2021) - Sun, Bangyong; Zhao, Yi; Wu, Weimin; Zhao, Qiang; Li, Gang
Abstract: Hanging drop (HD) is one of the most popular methods used for forming three-dimensional (3D) cell spheroids. However, conventional hanging drop systems are only applicable for short-term spheroid culture due to their inconvenience in exchanging cell culture media. Here we present a medium-reservoir-integrated superhydrophobic (MRI-SH) chip for long-term HD spheroid cultures. The device consists of two main components: i) a patterned superhydrophobic (SH) surface containing an array of wettable spots which anchor arrays of droplets of cell suspension, and ii) an array of chambers that serve as medium reservoirs, both interconnected via an array of thru-holes. This configuration provides two distinct advantages over conventional HD configurations: i) the high wettability contrast of the SH pattern on the chip leads to the formation and adhesion of nearly spherical hanging droplets on its surface, which minimizes interactions between the liquid and the substrate; ii) the integrated chambers provide large volumes of medium to maintain longer culture durations. Using this device, spheroids of MHCC97H cells were successfully formed, and the cultured spheroids could maintain high viability for up to 30 days and exhibited enhanced spheroid morphology compared to those cultured in the conventional HD systems. Statement of significance: This paper presents a medium-reservoir-integrated superhydrophobic hanging drop (HD) platform for the long-term culture of spheroids with enhanced morphology. By monolithically integrating medium reservoirs and a patterned SH surface into a single device, this HD platform can not only produce high-quality spheroids, but also permit them to sustain high viability for up to 30 days without the need for tedious medium replenishment. We believe that such a platform will be valuable in a wide range of biological or biomedical applications, including tissue engineering, regenerative medicine, and drug discovery. Graphical abstract: Image, graphical abstract